8-2x=6x+3

Simple and best practice solution for 8-2x=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-2x=6x+3 equation:


Simplifying
8 + -2x = 6x + 3

Reorder the terms:
8 + -2x = 3 + 6x

Solving
8 + -2x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
8 + -2x + -6x = 3 + 6x + -6x

Combine like terms: -2x + -6x = -8x
8 + -8x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
8 + -8x = 3 + 0
8 + -8x = 3

Add '-8' to each side of the equation.
8 + -8 + -8x = 3 + -8

Combine like terms: 8 + -8 = 0
0 + -8x = 3 + -8
-8x = 3 + -8

Combine like terms: 3 + -8 = -5
-8x = -5

Divide each side by '-8'.
x = 0.625

Simplifying
x = 0.625

See similar equations:

| n-a=b | | -4.1+x=0 | | 14b-19=5 | | 6-6x-2=3(3x+1) | | 6x-(2x+5)=27 | | 9000(x+0.3)-8000x=47 | | -3-4x=-4 | | j/3+8=10 | | 5y+3=4y-4 | | 7x+9-3x=10-11x-12 | | 8m^3-27h^3= | | 2x+(x+60)=180 | | 9-7x=65-21x | | 7+9+x=8+8 | | 5x-85+8x=162 | | 1.7=1.7t+at | | 3x+5+3x+5=6x+15 | | 2=x/8 | | 2x+20=3x-14 | | 3s+3=9 | | Ab-bc=d | | 5a+3b=30 | | 10+2k=16 | | -3+q=5 | | 36+37+38=w | | 4=g/3+3 | | (X+5)(x^2-4)=0 | | 5x-16=2x-4 | | 36+35+37=x | | 5x-25+8x=27 | | 4x^2+12=19x | | -15x+1+7x=3-8x |

Equations solver categories